Description of Iron, Protein Intake, Compliance with Government Activity Blood Supplement Tablets Consumption and Consumption Patterns of Iron Inhibitors in Adolescent Girls at Public High School 1 Barat Magetan District - Gegiyansari; Inne Soesanti; Ani Intiyati; Erlyna Jayeng Wijayanti (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Anemia is common in developing countries such as Indonesia. Government prevention efforts to overcome iron deficiency are by giving Blood Addition Tablets and also improving diet. Identify the intake of protein iron consumption, compliance consumption of government activity blood supplement tablets and consumption patterns of iron inhibitors in SMA Negeri 1 Barat Magetan District. This research is a descriptive study. Data collection by interview with a questionnaire instrument compliance consumption of blood supplement tablets and food intake interview with SQ-FFQ questionnaire. The number of respondents was 58 students with proportional random sampling technique. The percentage of students who did not consume blood supplement tablets (67.2%). The level of iron intake was deficient (62.1%), students consumed tannin very often (25.9%), consumption of phytic acid often (48.3%), and the level of protein intake was severely deficient (79.3%). Most students did not consume the given blood supplement tablets. Most students had iron deficiency and protein intake levels that were severely deficient. The students also had a frequent category in consuming phytic acid and also had a frequent category in consuming phytic acid. Schools are advised to hold counseling on anemia and balanced nutrition, and blood supplement tablets supplementation activities.